2020
DOI: 10.3389/fmed.2020.589553
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Aging in Acute Respiratory Distress Syndrome: A Clinical and Mechanistic Overview

Abstract: Acute respiratory distress syndrome (ARDS) is associated with increased morbidity and mortality in the elderly population (≥65 years of age). Additionally, age is widely reported as a risk factor for the development of ARDS. However, the underlying pathophysiological mechanisms behind the increased risk of developing, and increased severity of, ARDS in the elderly population are not fully understood. This is compounded by the significant heterogeneity observed in patients with ARDS. With an aging population wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 106 publications
(128 reference statements)
0
13
0
Order By: Relevance
“…Thus, counteracting the cell senescence process or eliminating senescent lung cells might lessen lung damage severity. This may be of therapeutic importance as strategies are now proposed to control senescence in various lung diseases, as well as in acute respiratory distress syndrome due to other causes ( 13 , 14 ). A recent study in mice showed that lung inflammation caused by a mouse β-coronavirus was markedly reduced by senolytic treatment, which also decreased mortality in old mice ( 7 ).…”
mentioning
confidence: 99%
“…Thus, counteracting the cell senescence process or eliminating senescent lung cells might lessen lung damage severity. This may be of therapeutic importance as strategies are now proposed to control senescence in various lung diseases, as well as in acute respiratory distress syndrome due to other causes ( 13 , 14 ). A recent study in mice showed that lung inflammation caused by a mouse β-coronavirus was markedly reduced by senolytic treatment, which also decreased mortality in old mice ( 7 ).…”
mentioning
confidence: 99%
“…Thus, an independent association between the development PGD and donor age remains unclear. More studies will be required, but it is difficult to ignore the possibility that donor age is relevant, especially considering that increasing age is associated with enhanced susceptibility to ARDS 29,30 …”
Section: Donor Factors Implicated In Development Of Pgdmentioning
confidence: 99%
“…Chemotaxis, phagocytosis, microbial killing, and NET formation are impaired in neutrophils of older individuals. Further, endothelial permeability regulated by Ang2 is higher in older lungs and NADPH oxidase 4 (ROS production) upregulated [ 7 ]. Animal data showed higher CD80 and CD86 expression upon lipopolysaccharide (LPS) challenge in older mice and increased MIF-1α levels, whereas antigen presentation and bacterial and viral clearance were decreased.…”
Section: Lung Changes In Ardsmentioning
confidence: 99%
“…The incidence of ARDS is lower in 15–19-year-old individuals (16/100,000 person-years) compared to 75–84-year-old persons (306/100,000 person-years) [ 6 ]. Among the hospitalized patients, there was, however, no clear difference regarding admission to ICU, ventilation length, and length of hospitalization between patients younger or older than 65 y [ 7 ]. Neonatal ARDS is due to immaturity of the lung, and standard treatment consists of the administration of an exogenous surfactant.…”
Section: Introductionmentioning
confidence: 99%